2017
DOI: 10.1038/s41467-017-00182-7
|View full text |Cite
|
Sign up to set email alerts
|

HDAC3 is a molecular brake of the metabolic switch supporting white adipose tissue browning

Abstract: White adipose tissue (WAT) can undergo a phenotypic switch, known as browning, in response to environmental stimuli such as cold. Post-translational modifications of histones have been shown to regulate cellular energy metabolism, but their role in white adipose tissue physiology remains incompletely understood. Here we show that histone deacetylase 3 (HDAC3) regulates WAT metabolism and function. Selective ablation of Hdac3 in fat switches the metabolic signature of WAT by activating a futile cycle of de novo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 49 publications
8
57
0
Order By: Relevance
“…A previous report has shown that HDAC3-deficient mice underwent significant re-modelling of the WAT metabolic pathway to resemble BAT (browning) without β-AR stimulation [13]. This study thus highlights a negative regulation of HDAC3 to WAT browning.…”
Section: Discussionsupporting
confidence: 59%
“…A previous report has shown that HDAC3-deficient mice underwent significant re-modelling of the WAT metabolic pathway to resemble BAT (browning) without β-AR stimulation [13]. This study thus highlights a negative regulation of HDAC3 to WAT browning.…”
Section: Discussionsupporting
confidence: 59%
“…Exposure to the cold [16-18] or selective ADRB3 agonists [7] resulted in higher resting metabolic rate and hBAT activity in healthy individuals as measured via 18 F-FDG/PET-CT, in whom the ADRB3 pathway was considered as a dominant signaling pathway to promote the activation or differentiation of beige adipocytes [17, 19, 20]. ADRB3 belong to G protein-coupled receptors and are abundant in adipose tissue, especially in the BAT [17, 21]. Trp64Arg polymorphisms of ADRB3 genes are associated with a variety of body weight [22, 23].…”
Section: Discussionmentioning
confidence: 99%
“…For example, HDAC1 has been shown to associate with regulatory elements of BAT-specific genes, resulting in reduced histone H3K27 acetylation and consequent transcriptional repression (38). Another class I HDAC, HDAC3, has also been linked to the regulation of BAT gene expression and thermogenesis in mice (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%